Measuring the sitting posture of high school learners, a reliability and validity study - Van Niekerk, Sjan-Mari (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScPhysio (Physiotherapy))--University of Stellenbosch, 2007.